A Visualization Tool Used to Develop New Photon Mapping Techniques - Mark Jones (Computer Graphics Forum, 2015)
We present a visualisation tool aimed specifically at the development and optimisation of photon map denoising methods. Our tool allows the rapid testing of hypotheses and algorithms through the use of parallel coordinates, domain-specific scripting, color mapping and point plots. Interaction is carried out by brushing, adjusting parameters and focus-plus-context, and yields interactive visual feedback and debugging information. We demonstrate the use of the tool to explore high-dimensional photon map data, facilitating the discovery of novel parameter spaces which can be used to dissociate complex caustic illumination. We then show how these new parameterisations may be used to improve upon pre-existing noise removal methods in the context of the photon relaxation framework.